Peningkatan Kemampuan Kognitif dan Sosial Siswa melalui Metode Think-Pair-Share di SD - Ima Rosila; Muhlisin Muhlisin; Abdul Khobir (Lembaga Pengembangan Kinerja Dosen, 2025)
Cooperative Learning has been proven effective in improving the quality of education, especially at the elementary school level. One popular cooperative learning model is the Think-Pair-Share (TPS) method. This method provides students with the opportunity to think independently, discuss with a partner, and share their thoughts with the larger group. This study aims to explore the optimization of the implementation of the TPS method in enhancing the cognitive and social abilities of elementary school students. Using a descriptive qualitative approach, this study analyzes how the implementation of TPS can affect students' understanding of the material as well as their social skills. The results indicate that the application of the TPS method not only improves students' cognitive abilities, such as mastery of subject matter and critical thinking skills, but also strengthens their social skills in interacting, communicating, and collaborating with classmates. This study recommends the integration of the TPS method into elementary school teaching practices to maximize students' potential in various aspects, both cognitive and social.